The effectiveness of resistance to torsional loads of various options for osteosynthesis of bone fragments of the tibia for fractures in the upper third of the diaphysis (mathematical modeling) - Karpinsky, Mykhaylo; Stroiev, Maksym; Berezka, Mykola; Hryhoruk, Viktoriia; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The treatment of patients with tibial fractures and overweight has certain peculiarities due to the increased load on the osteosynthesis device. Objective. To compare the stress-strain state of models of the lower leg with a fracture of the tibia in the upper third of the diaphysis under the influence of torsional load under different options of osteosynthesis depending on the patient's weight. Methods. Using the finite element method, a fracture in the upper third of the tibia and three types of osteosynthesis were modeled: using an external fixation device (EFD), a bone plate, and an intramedullary rod. A torque of 7 Nm and 12 Nm was applied to the tibial plateau. The results. The highest indicators of the stress level in the fracture zone (6.3‒10.8 MPa) and on the metal structure (251.0‒430.2 MPa) were determined in the model with a bony plate. In the model with osteosynthesis with the help of EFD, a fairly low stress level (0.2‒0.3 MPa) was established in the fracture zone, but a high one in the proximal part of the tibia (6.7‒11.5 MPa). The lowest values of stresses in the fracture zone (0.1‒0.2 MPa) and the proximal fragment of the tibia (0.6‒1.0 MPa) were determined under the conditions of reproduction of osteosynthesis using an intramedullary rod, but in the distal part of the tibia the stresses remained quite high — 11.1‒19.0 MPa. Conclusions. The values of stresses in the fracture zone in the models with EFD and intramedullary rod were significantly lower than the values of the intact bone, with the periosteal plate - only at a load of 7 Nm. In the distal fragment of the tibia, the highest stress level was determined in the model with osteosynthesis with an intramedullary rod, in the proximal one — with EFD. Among the metal structures, the greatest stresses were found in the periosteal plate and around the fixing screws and rods under the conditions of its use. The function of the dependence of the amount of stress on the weight of the patient in the elements of the model turned out to be linear and directly proportional.